Analisis pengaruh informasi laba terhadap perilaku investor di pasar sekunder - Farichah, Farichah (Jurnal Akuntansi, 2018)
After going through initial public offering process, the company must trade its shares in the secondary market. Companies should conduct signaling to users, such as investors and potential investors by providing information that can be utilized as a basis for investment decision making. The information announced (which includes earnings information) is expected to have a quality that allows investors and potential investors to predict company performance in the future. This study was conducting to investigate investors behaviour by observing trading volume, stock returns and earnings response coeffesient (ERC) in the short and long term. This study uses data and samples from the Indonesia Stock Exchange from 2006 to 2015. Hypothesis testing is done by using multiple linear regression and independent sample t test. The result showed that earnings information give effect to trading volume, stock returns, and ERC in short term (one year after IPO) and long term (for 5 years or more after IPO). The next result in the short term the stock trading volume, stock returns, and ERC is greater when compared with the volume of stock trading, stock returns, and ERC in the long term.